An Unusual Presentation of Multiple Superficial Mucoceles Occurring with Oral Lichen Planus - Dulyapong Rungraungrayabkul; Puangwan Lapthanasupkul; Naruemon Panpradit; Nis Okuma (Hindawi Limited, 2021)
Superficial mucoceles, a rare variant of the mucocele occurring simultaneously with oral lichen planus, are uncommon. This report introduces a case of multiple superficial mucoceles developing with oral lichen planus in a 76-year-old Thai female and provides information to avoid misdiagnosis and over-management of this lesion. Pathogenesis and clinicopathological characteristics of this phenomenon are also discussed.